2017
DOI: 10.1155/2017/8282391
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Specific Immunotherapy in Advanced Pancreatic Cancer: A Systematic Review and Meta-Analysis

Abstract: Specific immunotherapies, including vaccines with autologous tumor cells and tumor antigen-specific monoclonal antibodies, are important treatments for PC patients. To evaluate the clinical outcomes of PC-specific immunotherapy, we performed a systematic review and meta-analysis of the relevant published clinical trials. The effects of specific immunotherapy were compared with those of nonspecific immunotherapy and the meta-analysis was executed with results regarding the overall survival (OS), immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…An interesting meta-analysis gathering all clinical trials with immunotherapies in pancreatic cancer [ 136 ] found out that this strategy indeed significantly increases the 3-, 6-, 12-month and 3-year OS of patients. Importantly, immunotherapy significantly increases the immune response of patients with PDA and reduced CA19-9 levels.…”
Section: Pda and Immunotherapymentioning
confidence: 99%
“…An interesting meta-analysis gathering all clinical trials with immunotherapies in pancreatic cancer [ 136 ] found out that this strategy indeed significantly increases the 3-, 6-, 12-month and 3-year OS of patients. Importantly, immunotherapy significantly increases the immune response of patients with PDA and reduced CA19-9 levels.…”
Section: Pda and Immunotherapymentioning
confidence: 99%
“…A recent meta-analysis of specific immunotherapy trials employed in treatment of pancreatic cancer revealed that circulating IFN-gamma levels were significantly higher post-treatment versus pre-treatment (4 trials with 81 patients; pooled mean difference of 3.75 IU/mL; p=0.01), and circulating IL-4 levels were significantly lower (2 trials with 55 patients; pooled mean difference of −1.85 IU/mL; p<0.0001) [100]. Anti-tumor immunomodulatory effects are most likely maximized with multi-modal non-specific and specific immune therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies of effective immunotherapy, the development of antibodies to tumor-associated antigens has been associated with a positive response ( 23 , 24 ). However, the importance of antibodies as a component of effective antitumor responses has long been recognized ( 25 ). In this study, ranitidine is thought to function at least in part through modulation of tumor-associated immune suppression and would be predicted to impact multiple arms of acquired immune function, including antibody development.…”
Section: Discussionmentioning
confidence: 99%